PERFORMA LITTER KELINCI-INDUK LOKAL YANG DIBERI PAKAN HIJAUAN UBI JALAR DISUPLEMENTASI SEJUMLAH KONSENTRAT BERBEDA - Tarsono Tarsono; Najamudin Najamudin; Mustaring Mustaring; Yulius Duma; Supriono Supriono (Universitas Tadulako, 2009)
The study to identify the effects of different concentrate supplementation on the reproductive performance of the local rabbits fed with basal ration (i.e.: sweet potato forages – ad libitum) was carried out in Jono Oge village - Biromaru, Donggala–Central Sulawesi. The study used 12 multifarious does which were allocated to four treatments using a Randomized Block design (RBD). The treatments were as follows: does fed with basal ration (R0); does fed with basal ration supplemented with concentrate at 1% (R1), 2% (R2), and 3% (R3) of body weights. Litter sizes, weights at birth and weaning of kids were then recorded. Results showed that concentrate supplementation for the local rabbits fed with basal ration of sweet potato forages did not significantly affect the litter size and birth-weight of kids but the treatments did significantly affect their weaning-weights (21 day old).